The In-between Expression: Interpreting the Ambiguity of Islamic Culture in Bolaang Mongondow, North Sulawesi - Abdul, Moh. Rivaldi (Center for Research and Development of Religious Literature and Heritage, 2024)
This article interprets the encounters between various elements—Islam and rites, syarak and custom, and the profane and sacred—in the development of Islam in Bolaang Mongondow, North Sulawesi. The interpretation is based on the theoretical framework of cultural ambiguity. By exploring the tolerance of ambiguity, compromise solutions, and divergent meanings, this study aims to reveal religious expressions that embody an